Microstructure and Mechanical Properties of Carbon Fiber Phenolic MatrixComposites containing Carbon Nanotubes and Silicon Carbide - Subhani, Tayyab (Engineering, Technology & Applied Science Research, 2024)
A novel class of hybrid composites was prepared containing carbon fibers along with carbon nanotubes and silicon carbide particles in phenolic resin for improved mechanical performance. The loading of carbon fibers was 60 wt% while carbon nanotubes and silicon carbide particles were reinforced in the fractions of 0.1 wt% and 5 wt%, respectively. Individually reinforced composites containing 0.1 wt% carbon nanotubes and 5 wt% silicon carbide particles were also manufactured for comparison with hybrid composites. Microstructural and mechanical property characterization was performed using electron microscopy and mechanical testing, respectively. Uniform dispersion of nanometer-scale carbon nanotubes and micrometer-scale silicon carbide particles was observed under microscopy. The pooled effect of carbon nanotubes and silicon carbide particles significantly increased the tensile, compressive, and flexural performance of composites while carbon nanotubes offered greater weight fraction value improvement than silicon carbide particles.